(untitled) (Research, Society and Development, 2022)
Metal nanoparticles have varied uses in different fields of application, such as AgNPs, silver nanoparticles, which have antibacterial, antiviral and antitumor properties. Demonstrating numerous competitive advantages over the traditional chemical route, the process of obtaining AgNPs by “green route” has aroused the interest of the scientific community around the world. Given the scarcity of publications that jointly analyze the patents related to the subject, the objective of the present work was to develop a descriptive and exploratory study from the study of patents of processes of green synthesis of AgNPs deposited in the platforms INPI, Espacenet, USPTO, Latipat and Google Patents. As a result, Saudi Arabia occupies the first place among the depositor countries, with Brazil in the second position in the world and first in Latin America. Considering the rich plant biodiversity and the number of published scientific articles, Brazil has great potential to assume world leadership, as long as there is greater investment in the intellectual protection of products or technological processes obtained. Furthermore, it was observed that 100% of the deposits originating in Brazil were submitted by University Institutions, predominating the use of naturalized plant species or cultivated in Brazilian soil. It is concluded that there is a need to expand the protection of findings arising from the exploitation of the Brazilian natural heritage, the need for investments in research outside the academic scope and the relevance of this compiled as a useful document for consultation regarding the state of the art, prior to the proposition of research projects or technological development related to the production of AgNPs by green synthesis routes.